A case study of ownership and use of air conditioning in a tropical urban area and its impact on energy consumption / Shit Mun Chuan - Shit , Mun Chuan (2021)
Malaysia, a tropical country had experienced a drastic increase of air conditioner ownership in the past few decades, data from market demand also suggest that the growth would maintain an upward trend in the future. This study aims to review on the trend of households’ ownership of air conditioners (AC) and the energy consumption of AC in residential and non-residential area. The selected area of study is Petaling Jaya, a tropical urban environment. Due to the rejection of waste heat from the air conditioner cooling process, it is suggested that there would be an increase in outdoor temperature where air conditioner is in used. This rise of temperature causes a higher average temperature in the urban area. Additionally, it is suggested that this will also increases the usage of air conditioning to maintain the thermal comfort of the indoor environment. This study also recommended alternative cooling methods in an urban area such as a building structure design, ventilation, increase vegetation, green roof and cool roof was recommended.